A Pluralistic Perspective on Research in Psychotherapy: Harnessing Passion, Difference and Dialogue to Promote Justice and Relevance - Smith, Kate; McLeod, John; Blunden, Nicola; Cooper, Mick; Gabriel, Lynne; Kupfer, Christine; McLeod, Julia; Murphie, Marie-Clare; Oddli, Hanne Weie; Thurston, Mhairi; Winter, Laura Anne (Frontiers in Psychology, 2021)
The adoption of a pluralistic perspective on research design, processes of data collection and analysis, and dissemination of findings, has the potential to enable psychotherapy research to make a more effective contribution to building a just society. A review of the key features of the concept of pluralism is followed by a historical analysis of the ways in which research in counseling, psychotherapy and related disciplines has moved in the direction of a pluralistic position around knowledge creation. Core principles of a pluralistic approach to research are identified, and explored in the context of a critical case study of contemporary research into psychotherapy for depression. Implications of a pluralistic perspective for research training and practice are discussed. Pluralistic inquiry that emphasises dialogue, collaboration, epistemic justice and the co-existence of multiple truths, creates opportunities for individuals, families and communities from a wide range of backgrounds to co-produce knowledge in ways that support their capacities for active citizenship and involvement in open democratic decision-making. To fulfil these possibilities, it is necessary for psychotherapy research to be oriented toward social goals that are sufficiently relevant to both researchers and co-participants to harness their passion and work together for a common good.